1980
DOI: 10.1177/106002808001400904
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Crystallization of Phenytoin in Normal Saline

Abstract: A study was designed to determine if the admixture of phenytoin in normal saline would remain physically stable for a suitable period of time to allow for intravenous infusion. Five phenytoin concentrations (1.0 mg/ml, 2.5 mg/ml, 5.0 mg/ml, 7.5 mg/ml, and 10.0 mg/ml) were prepared in triplicate by adding a sufficient volume of normal saline to the appropriate volume of phenytoin sodium injection to produce a total volume of 100 ml. Aliquots of all solutions were withdrawn at zero, 1, 8, 16, and 24 hours. Solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
(4 reference statements)
1
5
0
Order By: Relevance
“…Although the exact pH value was not determined, because of its unstable pH, no precipitation was observed for at least 24 h in this admixture (data not shown). Many authors stated that phenytoin sodium injection in saline, but not in glucose infusion fluid, is stable for hours; 8,10,14,15,18) our results agree well with this contention.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although the exact pH value was not determined, because of its unstable pH, no precipitation was observed for at least 24 h in this admixture (data not shown). Many authors stated that phenytoin sodium injection in saline, but not in glucose infusion fluid, is stable for hours; 8,10,14,15,18) our results agree well with this contention.…”
Section: Discussionsupporting
confidence: 90%
“…[8][9][10][11]14,15) From investigation using a glucose infusion fluid admixture, 8) Pfeifle et al insisted on the existence of crucial factors that are not associated with pH reduction. Regarding other fluids, such as saline and lactated Ringer's injection, their enhancement effect on the precipitation of phenytoin is doubtful: the majority of authors rejected their ability to induce precipitation, 8,10,14,15,18) whereas some authors reported opposite results. 11,12) In this study, first we characterized the precipitation occurring after mixing phenytoin sodium injection with glucose infusion fluids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there are many studies indicating that the admixture diluted with saline is stable for many hours. 11,12,14,17,18) We also observed no crystallization from the admixtures as long as the injection was diluted with saline or water. 19) In the previous study, we have investigated the crystallization that occurs upon mixing with glucose-containing infusion fluid.…”
mentioning
confidence: 56%
“…The influence of various factors other than the final pH of the admixture has been investigated. These factors include dilution of the phenytoin solubilizing agent by infusion fluids, [11][12][13] particulate matter present in infusion fluids, 13) time delay from the dilution, 12,14) and solvent evaporation and absorption of carbon dioxide when the solution is exposed to air. 15,16) Despite the best endeavors, there are still some unknown factors associated with the crystallization from phenytoin sodium injection occurring after mixing with infusion fluids.…”
mentioning
confidence: 99%